النزعات الباطنية التحريفية وأثرها في الواقع الديني-الإجتماعي لبروناي دار السلام /cإعداد، نور عرفان بن حاج زينل - Norarfan Haji Zainal, Awang (Kulliyyat Ma'arif al-Wahy wa al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah, 2010)
This study examines the current state and development of the Batiniyyah thought in Brunei Darussalam based primarily on the fieldwork data obtained from a number of deviant individuals and groups that were influenced by the doctrine and principles of Batiniyyah. In addition, it also examines some of the writing that contain the Batiniyyah speculative interpretations that have gained some footing in Brueian society, and these were found to be full of symbolisms and allegory. The effect of this infiltration is then analysed in terms of the impact it had on the religious and social aspects of the Bruneian people. The study found that this infiltration has a major impact in shaking the foundation of the authentic doctrine of Islam, undermining the position of the Islamic sacred texts and the observation of Islamic ethical principles among the Muslims, and threatening the security and stability of the state. Finally, the position of the Brunei government in facing the challenges and threats posed by the Batiniyyah thought is evaluated and analysed against the factors that made such a doctrine appealing to some segments of the society. In light of that, some possible solutions to deal with it are also presented.